2022
DOI: 10.1002/jper.21-0621
|View full text |Cite
|
Sign up to set email alerts
|

The additive effect of periodontitis with hypertension on risk of systemic disease and mortality

Abstract: Background: Recent evidence suggests that periodontitis (PD) causes hypertension, which is a precursor to development of other systemic diseases. The aim of this study was to examine the effect of hypertension and PD on the risk of subsequent systemic disease. Methods:This longitudinal cohort study included 244,393 UK Biobank participants who were free of systemic disease other than hypertension at baseline. Self-reported responses of painful gums or loose teeth were surrogates for PD. Hypertensives were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Our findings are consistent with earlier evidence that periodontitis increased the risk of all-cause mortality in the older population in Sweden and Denmark and in hypertensive patients (Hansen et al 2016; Bengtsson et al 2021; Larvin et al 2022). Nevertheless, it is not easy to compare these studies, as they applied slightly different definitions for periodontitis.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with earlier evidence that periodontitis increased the risk of all-cause mortality in the older population in Sweden and Denmark and in hypertensive patients (Hansen et al 2016; Bengtsson et al 2021; Larvin et al 2022). Nevertheless, it is not easy to compare these studies, as they applied slightly different definitions for periodontitis.…”
Section: Discussionsupporting
confidence: 93%
“…These conditions can induce a state of systemic inflammation, which is in line with what Ramadan et al (2020), and Passarelli et al (2020), have concluded on the given topic [ 48 , 49 ]. The bioactive molecules released during this chronic low-grade inflammation, such as cytokines, can adversely affect vascular endothelial function, setting the stage for increased arterial stiffness and hypertension [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is independently associated with multi-morbidity [21]. Furthermore, hypertensive patients with periodontitis have an increased risk of several systemic diseases, especially CVD and respiratory disease [22]. The recognized association between periodontitis and hypertension, and the possibilities for interventions are essential considering the high prevalence of both diseases and increased societal burden of underdiagnosed and undertreated periodontitis.…”
Section: Discussionmentioning
confidence: 99%